Key performance indicators for maintenance of health-care facilities - Shohet, Igal M (Facilities (Bradford, West Yorkshire, England), 2003)
Maintenance management of health care facilities is one of the more complex subjects in the field of maintenance. The performance of hospital buildings is affected by numerous factors, including quality of hospital maintenance, actual occupancy vs standard occupancy, age of buildings, surrounding infrastructures, etc. The purpose of this research was to quantify the effects of users, building parameters and systems on the performance and maintenance of hospital buildings. The following factors were investigated: overall performance of the building; age of the building; level of building occupancy; and extent of labor outsourcing. The effects of the above parameters and variables were examined and quantified, employing coefficients and diagrams, using analytical and statistical analysis. The coefficients and diagrams developed were integrated into four key performance indicators for hospital buildings. The model was tested on six case studies, one of which is presented here.